The Arabic prose poem : poetic theory and practice - Fakhreddine, Huda J. (Edinburgh studies in modern Arabic literature., 2021)
The Arabic prose poem gave rise to a profound, contentious and continuing debate about Arabic poetry: its definition, its limits and its relation to its readers. Huda J. Fakhreddine examines the history of the prose poem, its claims of autonomy and distance from its socio-political context, and the anxiety and scandal it generated. When the modernist movement in Arabic poetry was launched in the 1940s, it threatened to blur the distinctions between poetry and everything else. The Arabic prose poem is probably the most subversive and extreme manifestation of this blurring. It is often described as an oxymoron, a non-genre, an anti-genre, a miracle and even a conspiracy"--